Design of Backhual Radio System for Outdoor to Indoor Signal Distribution - Lway Faisal Abdulrazak (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
A simple design of integrated system for wireless backhaul network that can work as a wireless bridge and access point had been developed in this paper. This system has a circular polarization (CP) patch antenna built for IEEE 802.11b/g standard (2.4GHz ~ 2.4835 GHz frequency band) and intended to point to multi point link. Another antenna is designed on frequency range 5.725 ~ 5.825GHz unlicensed band IEEE802.11a standard to point to point link. Therefore, two antennas on different frequencies and polarizations have been developed and finally incorporated on one router board. First antenna is a single-feed microstrip. The antenna substrate has an air-layer with thickness about 2.5% of the wavelength at a resonant operating frequency. The two truncated opposite corners technique are used to obtain the circular polarized operation by selecting an optimal size of truncating. A flat ground plane with an optimal position for the probe pin is used to generate an impedance matching with a wide bandwidth. Measured -10dB bandwidth is 14.3%, maximum gain and half-power beamwidth are, -41dB, 8.3 dBi, 60° respectively. Second antenna used is Radial Waveguide Slot Array Antenna (RWSA), which is directional antenna and used for main internet source. Return loss, gain and radiation pattern simulated by software which is developed on Borland C++ 5.0. Tests were setup in different environments, in the lab and outdoors and practical measurements have been taken to validate the simulation results and performance. The proposed design can find its applications in wireless communication systems, especially where cost-effective high-speed wireless Internet access service is required.